Persuasive technology contributions toward enhance information security awareness in an organization - Qudaih, Hani A.; Bawazir, Mohammed A.; Usman, Shuaibu Hassan; Ibrahim, Jamaludin (IJCTT Journal, 2014)
Persuasion is part and parcel of human interaction. The human persuaders in society have been always exit, masters of rhetoric skilled of changing our minds, or at least our behaviors. Leaders, mothers, salesmen, and teachers are clear examples of persuaders. Persuaders often turn to technology and digital media to amplify their persuasive ends. Besides, our lives and how we lead them influenced by technologies and digital media, but for the most part, their effects on our attitudes and behaviors have been incidental, even accidental. Although, nowadays, the use of computers to sell products and services considered as the most frequent application of persuasive technology. In this short paper, based on an extensive review of literatures, we aim to give a brief introduction to persuasive technology, and how it can play a role and contribute to enhance and deliver the best practice of IT. Some challenges of persuasive technology have been discussed. At the end, some recommendations and steps should be taken place to empower IT professional practices have been listed.